VD_FINDINFO Décision / 2013 / 699 vom 2. August 2013 - VD Tribunal cantonal (2013)
NON-LIEU, FRAIS DE LA PROCÉDURE, DÉPENS, AVOCAT, HONORAIRES | 426 al. 1 CPP (CH), 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH), 429 al. 1 let. c CPP (CH), 429 CPP (CH)